2019
DOI: 10.1177/0959683619875193
|View full text |Cite
|
Sign up to set email alerts
|

Holocene atmospheric dust deposition in NW Spain

Abstract: Atmospheric dust plays an important role in terrestrial and marine ecosystems, particularly those that are nutrient limited. Despite that most dust originates from arid and semi-arid regions, recent research has shown that past dust events may have been involved in boosting productivity in nutrient-poor peatlands. We investigated dust deposition in a mid-latitude, raised bog, which is surrounded by a complex geology (paragneiss/schist, granite, quartzite and granodiorite). As proxies for dust fluxes, we used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Halogens have been used as indicators of increased sea salt spray during storms (Orme et al, 2015;Stewart et al, 2017), although this has not shown to be universally applicable (Kylander et al, 2020). Multi-element approaches have also revealed changes in the source, grain size and magnitude of minerals being deposited on bogs through, for example, Si/Al ratios and elemental MAR (Kylander et al, 2020;Martinez-Cortizas et al, 2020;Sj€ ostr€ om et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Halogens have been used as indicators of increased sea salt spray during storms (Orme et al, 2015;Stewart et al, 2017), although this has not shown to be universally applicable (Kylander et al, 2020). Multi-element approaches have also revealed changes in the source, grain size and magnitude of minerals being deposited on bogs through, for example, Si/Al ratios and elemental MAR (Kylander et al, 2020;Martinez-Cortizas et al, 2020;Sj€ ostr€ om et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The 8.2 ky BP event has not been detected, although it has been found several times in the N and NW Iberian Peninsula (González-Amuchástegui and Martínez-Cortizas et al, 2020). The homogeneity of AC-4 layer indicates that from 10.2 -10.1 ky BP.…”
Section: Figura 5 Comparación Del Depósito Ac Con Otros Depósitos Enmentioning
confidence: 94%
“…Peatlands are specific anoxic and acidic environments that have the potential to retain and store large amounts of major and trace elements [1,2]. Ombrotrophic peatlands are limited to the atmosphere as a source of water and mineral matter [3,4], and are believed to be good geochemical archives of air quality over the past centuries [1,5,6]. This is based on the assumption that trace elements are immobile in the peat matrix and that accumulation in the record represents a direct measure of atmospheric deposition [7,8].…”
Section: Introductionmentioning
confidence: 99%